Hospital Readiness Assessment for Disasters Using the Hospital Safety Index in Several Accredited Hospitals in Yogyakarta Province - Mufidatul Laily (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2020)
Indonesia is a disaster-prone country, so research on hospital preparedness for disasters is necessary. One of the tools to measure the readiness of hospitals in facing disasters using the Hospital Safety Index (HSI) from WHO. This study aims to determine the readiness of hospitals to deal with disasters using HSI. Research location in PKU Yogyakarta, PKU Bantul, PKU Kotagede, PKU Nanggulan, and PKU Wonosari. These PKU that have been accredited by the Hospital Accreditation Committee in Yogyakarta Province. The approach used is descriptive qualitative. The independent variable is the HSI from WHO, and the dependent variable is the Hospital Accreditation Committee (Komite Akreditasi Rumah Sakit/KARS) accredited hospital. The respondents are the person in charge of the structural part of the disaster management system. The checklist refers to the HSI form from WHO. Each statement provides three types of answers, namely low, medium, and high. All statements are a total number of low scores, medium scores, and high scores using the HSI calculator. The results of the study are that hospitals with plenary accreditation have higher HSI scores so that they prepared to face disasters than hospitals that have not been plenarily accredited.